2011
DOI: 10.1021/nn201169u
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Construction of Self-Standing Anodized Titania Nanotube Arrays and Nanoparticles for Efficient and Cost-Effective Front-Illuminated Dye-Sensitized Solar Cells

Abstract: We report on the influence of hierarchical structures, constructed via layer-by-layer assembly of self-standing titania nanotube arrays and nanoparticles, upon charge recombination and photoelectric performance of front-illuminated dye-sensitized solar cells. Both nanotubes and nanoparticles were produced by anodization rather than additionally employing other methods, providing low cost and great simplicity. Electrochemical impedance spectroscopy under AM 1.5 illumination indicates the construction of hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 31 publications
1
107
0
Order By: Relevance
“…Under such optimum conditions, the best conversion efficiency of front side illuminated TiO 2 nanotube based DSSCs is 8.0 % without additional particle decoration 361 , 9.1% after a TiCl 4 treatment, 660 and 9.8% after using bottom opened membranes 627 . Nevertheless, it should be mentioned that 88 TiO 2 nanoparticle layer under nanotubes in NT/NP/FTO solar cell configuration also highly contributes to the overall conversion efficiency, and only few studies clearly separate the effects of tube layers from nanoparticle layers 266 .…”
Section: Front-side Dsscsmentioning
confidence: 99%
“…Under such optimum conditions, the best conversion efficiency of front side illuminated TiO 2 nanotube based DSSCs is 8.0 % without additional particle decoration 361 , 9.1% after a TiCl 4 treatment, 660 and 9.8% after using bottom opened membranes 627 . Nevertheless, it should be mentioned that 88 TiO 2 nanoparticle layer under nanotubes in NT/NP/FTO solar cell configuration also highly contributes to the overall conversion efficiency, and only few studies clearly separate the effects of tube layers from nanoparticle layers 266 .…”
Section: Front-side Dsscsmentioning
confidence: 99%
“…34 As shown in Bode phase plots (Figure 6b), the medium-frequency peaks ( max ) are in the same order of C2 • C3…”
Section: Figurementioning
confidence: 64%
“…For example, Zheng et al reported the influence of hierarchical structures, constructed via layerby-layer assembly of self-standing titania nanotube arrays and nanoparticles, upon charge recombination and photoelectric performance of front-illuminated DSCs [64]. Both nanotubes and nanoparticles were produced by anodization rather than additionally employing other methods, providing low cost and great simplicity (Fig.…”
Section: Tio 2 Nanotubes Filmsmentioning
confidence: 99%
“…Both nanotubes and nanoparticles were produced by anodization rather than additionally employing other methods, providing low cost and great simplicity (Fig. 8) [64]. Electrochemical impedance spectroscopy under AM 1.5 illumination indicates the construction of hybrid morphology has superior recombination characteristics and a longer electron lifetime than nanoparticulate systems.…”
Section: Tio 2 Nanotubes Filmsmentioning
confidence: 99%